Analisis keselamatan dan kesehatan kerja (K3) pada pekerja di lingkungan Minas Gas Turbine (MGT) PT. Chevron Pacific Indonesia (CPI), Minas - Ali Amran; Bintal Amin; Sofia Anita (SEHATI: Jurnal Kesehatan, 2021)
Human resources play an important role for the success of an organization or company, because humans are living assets that need special attention by the company. The fact that humans as a major asset in an organization or company must get serious attention and be managed as well as possible. In managing human resources, management is needed to be able to manage resources systematically, planned and efficiently. Of the many companies that move at high levels of potential hazards, one of them is the Oil and Gas Mining sector and in this sector work accidents often occur. In general, accidents are always interpreted as "unexpected events". Actually, every work accident can be predicted or suspected from the beginning if the actions and conditions do not meet the requirements. Statistics reveal that 80% of accidents are caused by unsafe acts, and only 20% by unsafe conditions (Silalahi, 1991). Several studies in Indonesia have been carried out to analyze Occupational Safety and Health (K3) on other elements in the company, including in the oil, gas and geothermal sectors, but the results are not always significant. PT. Chevron Pacific Indonesia (PT. CPI) is one of the largest oil, gas and geothermal energy companies in Indonesia. Many sections or departments in CPI are high-risk, one of which is the Minas Gas Turbine (MGT) found in the PGT department. The problems that exist are how a Safe Work Culture, Worker Competence, Work Safety Procedures and Regulations, Management Commitment (Economy) and Work Environment affect the Work Safety of Employees in the Minas Gas Turbine section of PT. Chevron Pacific Indonesia, Minas. By definition a turbine is a rotating machine that takes energy from the fluid flow. Simple turbines have one moving part, "rotor-blade assembly". One of the functions of the Minas Gas Turbine (MGT) is currently for power plants and gas producers whose uses are for production areas, offices, housing and buildings that are located around the production area. PT. Chevron Pacific Indonesia and has a 115KV voltage electricity network that is spread for transmission lines from one area to another. This is very influential on the safety track record of workers who become operational support as a whole. By examining some of the components that exist as research variables, it can be concluded that a Safe Work Culture, Worker Competence and Work Environment really needs special attention by the Project Management Team (PMT) in the Minas Gas Turbine section around 27.7-31.3% While Work Safety Procedures and Regulations are a very strong variable influence on Employee Safety that is equal to 89.5%. And there is a strong influence between Management Commitment (Economy) on Employee Safety, which is 47.6%.